The Influence of Test Positions on Clinical Assessment for Scapular Dyskinesis. Issue 8 (1st December 2016) - Deng, Simin; Chen, Kang; Ma, Yanhong; Chen, Juan; Huang, Mi
Abstract: Background: Appropriate evaluation of scapular dyskinesis is essential for therapeutic strategies. Although the current visual‐based assessment is rapid and practical, the reliability of this method is unsatisfactory. It is necessary to adequately understand the conditions of assessment to maximize the benefit of therapeutic interventions. Objective: To explore the influence of different test positions on clinical assessment for scapular dyskinesis. Design: Observational study. Setting: University rehabilitation department. Patients: A total of 102 subjects diagnosed with unilateral shoulder disorder were recruited from among rehabilitation outpatients from November 2015 to February 2016. Methods: Two experienced raters categorized the subjects' scapular movement pattern according to Kibler et al classification by the vision‐palpation method at 4 test positions (at rest, and the end range of elevation in the sagittal, scapular, and coronal planes). Main Outcome Measurements: The overall prevalence of scapular dyskinesis, the distribution of types, and the reproducibility of types at the 4 test positions were analyzed. Results: The overall prevalence of scapular dyskinesis was 90.08%, and the highest frequency was found at the resting position. Type III was the most common type in our sample. In reproducibility analysis, 21.57% of subjects presented with the same type at any position, and 75.49% of subjects presented with 2 types. Conclusions: Scapular dyskinesis in individuals with shoulder disorder showed a high prevalence, especially at the resting position. More than 1 type of scapular pattern would be present if assessed at different positions. This study indicates that test positions can affect the results of scapular dyskinesis assessment, and that the resting position should primarily be applied. Level of Evidence: III